Polish version of the Aesthetic Experience Questionnaire: validation and psychometric characteristics - Świątek, Agata Hiacynta; Szcześniak, Małgorzata; Wojtkowiak, Karolina; Stempień, Michał; Chmiel, Marianna (Frontiers in Psychology, 2023)
Introduction The purpose of the article is to present the results of works on the Polish version of the Aesthetic Experience Questionnaire (AEQ). The AEQ is a 22-item tool for assessing aesthetic experience in the following dimensions: emotional, cultural, perceptual, understanding, and two dimensions about flow (proximal conditions and flow experience). Methods In the course of works on the Polish version of the AEQ, 3 independent studies with the participation of more than 800 people were carried out. In addition to the AEQ measurement, the tools included: the Emotion Regulation Strategies for Artistic Creative Activities Scale, the Brief Music in Mood Regulation, the Aesthetic Competence Scale, the Aesthetic Processing Preference Scale, the Need for Cognition Scale, the Center for Epidemiologic Studies - Depression Scale, the Material Values Scale and the Multidimensional Existential Meaning Scale. Results The results obtained in the three studies through Confirmatory Factor Analysis indicated the compliance of the factor structure of the Polish version of the AEQ with the original and its good psychometric characteristics. It was also shown that the overall result and individual components of the aesthetic experience correlate positively with emotion regulation through artistic creative activities and mood regulation through music, aesthetic competences (music, literature, plastic arts, film), cognitive curiosity and some dimensions of aesthetic processing preferences. The studies also proved a very weak positive relationship between aesthetic experience and meaning of life. The assumption about a negative correlation between aesthetic experience and depression or materialism was not confirmed. Discussion The Polish version of the AEQ is a credible psychometric measurement and encourages scientists to design research on the psychology of art and aesthetics in the Polish cultural conditions.